Role of Estrogen Receptor-β in Endometriosis - Bulun, Serdar E.; Monsavais, Diana; Pavone, Mary Ellen; Dyson, Matthew; Xue, Qing; Attar, Erkut; Tokunaga, Hideki; Su, Emily J. (Seminars in Reproductive Medicine, 2012)
Endometriosis is an estrogen-dependent disease. The biologically active estrogen, estradiol, aggravates the pathological processes (e.g., inflammation and growth) and the symptoms (e.g., pain) associated with endometriosis. Abundant quantities of estradiol are available for endometriotic tissue via several mechanisms including local aromatase expression. The question remains, then, what mediates estradiol action. Because estrogen receptor (ER)β levels in endometriosis are >100 times higher than those in endometrial tissue, this review focuses on this nuclear receptor. Deficient methylation of the ERβ promoter results in pathological overexpression of ERβ in endometriotic stromal cells. High levels of ERβ suppress ERα expression. A severely high ERβ-to-ERα ratio in endometriotic stromal cells is associated with suppressed progesterone receptor and increased cyclo-oxygenase-2 levels contributing to progesterone resistance and inflammation. ERβ-selective estradiol antagonists may serve as novel therapeutics of endometriosis in the future.
Keywords: ER-β; nuclear receptor; estrogen; DNA methylation; epigenetic; promoter; ER-α; PR